Trochlear calcification with coexisting orbital foreign bodies: case report and literature review. (2nd April 2014) - Salha, R.; Shah, J.; Sidebottom, A.J.
Abstract Asymptomatic radiodense opacities are commonly found on orbital computed tomography, and one of the causes is calcification of the trochlear apparatus. Distinction between anatomical calcifications and foreign bodies is particularly important in orbital trauma cases where misdiagnosis could lead to an inappropriate procedure. This case reports the coexistence of bilateral trochlear calcification and foreign body close to the orbit.